Method for preparing Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photoelectric detector
Through technical means such as pulsed laser deposition and high-temperature oxygen-passing annealing, a high-quality Cs3Cu2I5/ZnGa2O4 heterojunction structure was prepared, which solved the problems of low film quality and pollution in the existing technology, and improved the stability and performance of the photodetector. .
Patent Information
- Application Number
- CN202411358321.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, the film of the Cs3Cu2I5/ZnGa2O4 material is of low quality, the preparation method is complex and contaminated, resulting in poor stability and short life in actual applications, affecting the performance of optoelectronic devices.
Pulse laser deposition (PLD) technology used to bombard the ZnGa2O4 target in a high vacuum environment to form a film, and high-temperature oxygen annealing is performed through a tube furnace. Then, PLD technology is used to bombard the Cs3Cu2I5 target to form a film, and finally through electron beam vacuum thermal evaporation technology Au electrodes are evaporated to form a high-quality Cs3Cu2I5/ZnGa2O4 heterojunction structure.
It realizes the control of complex stoichiometric ratio, controllable film thickness, and vacuum in-situ growth, and obtains high-quality film materials, the preparation conditions are pollution-free and friendly, and the performance and stability of the photodetector are improved.
Smart Images

Figure CN119208449A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photoelectric detector, relates to the preparation of a perovskite / oxide semiconductor device, and belongs to the field of ultraviolet photoelectric detector preparation. Background Art
[0002] Photodetectors working in the ultraviolet region have the inherent ability to convert ultraviolet light signals into detectable electrical signals, and are widely used in biomedical detection, missile warning, space detection, flame detection, and confidential communications. Generally, deep ultraviolet photodetectors can be used as optical receivers in optical communication systems. Their recognition capabilities enable the contact network to have enhanced anti-interference, non-line-of-sight communication, and anti-interception capabilities. High-performance deep ultraviolet photodetectors are the key to the development of ultraviolet communication technology. Due to the day-blind ultraviolet light in the wavelength range of 200-280 nm, it is almost absorbed by the ozone layer. In recent years, great progress has been made in the research of day-blind ultraviolet detectors, which are mainly constructed using wide bandgap semiconductors such as Ga2O3, ZnMgO, ZnGa2O4, Cs3Cu2I5 and other materials.
[0003] The present invention proposes a method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector. At present, ZnGa2O4 has been widely studied due to its ultra-large band gap. The preparation of ZnGa2O4 thin film materials and their research in ultraviolet photoelectric devices are increasing, but there are few studies based on two wide band gap materials, and the detection range can be extended from UVC to the entire UVB band. Based on the band structure problem, the preparation of the ternary perovskite material Cs3Cu2I5 / ZnGa2O4 heterojunction structure is studied, and the Cs3Cu2I5 / ZnGa2O4 film is prepared by pulsed laser deposition (PLD) technology. After the growth of the ZnGa2O4 film, the gradient high temperature oxygen annealing is carried out through a tube furnace (CVD), and then the Au electrode is evaporated by electron beam vacuum thermal evaporation technology as the ohmic contact of the device.
[0004] At present, Cs3Cu2I5 / ZnGa2O4 materials are mostly prepared at home and abroad by metal organic chemical vapor deposition, magnetron sputtering and other methods. The preparation process is polluted, and the film surface has obvious holes and high roughness, making it difficult to obtain high-quality thin film materials. This causes the Cs3Cu2I5 / ZnGa2O4 heterojunction structure to have problems such as poor stability and short life in practical applications, which seriously affects its application in the field of optoelectronic devices. Summary of the invention
[0005] The invention provides a method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector, so as to solve the technical problems that the ZnGa2O4 and Cs3Cu2I5 films prepared by the prior art are of low quality, complicated preparation method and pollution.
[0006] The technical solution of the present invention is: A method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector comprises the following steps: S1: The preparation steps for thin film preparation are as follows: First, select a double-sided polished Al2O3 substrate and ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 5 minutes, 5 minutes, and 10 minutes respectively, in order to clean the dirt on the surface of the Al2O3 substrate. Then blow it dry with nitrogen, place it on the sample holder and fix it with metal, open the PLD injection chamber with high-purity nitrogen, place the Al2O3 substrate and the sample holder in it, open the water tank, the injection chamber mechanical pump, the injection chamber vacuum gauge, and the injection chamber molecular pump in turn, quickly pump the injection chamber to a high vacuum state, and then proceed to the next step of the experiment; S2: The preparation steps of ZnGa2O4 thin film are as follows: S21: The vacuum degree in the injection chamber reaches 6×10 -5 After the temperature is below Pa, the plate valves of the injection chamber-transfer chamber and the transfer chamber-preparation chamber are opened in sequence, and the Al2O3 substrate and the sample holder in S1 are placed in the preparation chamber; S22: Then, the temperature of the preparation chamber cavity and the substrate temperature are raised to 500°C using the temperature raising program L-MBE, the temperature raising current is adjusted to 5A (100°C / 1A), the temperature raising rate is controlled at 10°C / min, and the preparation chamber ionization vacuum gauge is turned off at the same time, and the 248nm excimer laser is turned on for preheating; S23: After the temperature rises to 500°C and stabilizes for 10 minutes, the laser preheating is completed, the pulse energy is adjusted to 320mJ, the frequency is set to 8Hz, and then the ZnGa2O4 target material is bombarded. The bombarded plasma plume is deposited on the surface of the Al2O3 substrate under high temperature environment. The deposition thickness is controlled to be 500nm by observing the film thickness monitor, and a ZnGa2O4 thin film sample on the Al2O3 substrate is obtained; S24: After the deposition is completed, the laser is first turned off, the temperature is set to 0°C, and the current is adjusted to 0A. After the temperature drops below 100°C, the ionization vacuum gauge ionization switch is turned on, and then the preparation chamber-transfer chamber and transfer chamber-injection chamber plate valves are opened in sequence to send the sample into the injection chamber. The molecular pump and mechanical pump are closed in sequence and filled with high-purity nitrogen, and then the sample obtained in S23 is taken out as a whole; S25: Place the sample taken out in S24 in a tube furnace (CVD), evacuate to a vacuum state, introduce high-purity oxygen, control the oxygen flow rate at 30 SCCM and stabilize for 15 minutes, then use a program to control the gradient temperature to 800°C, anneal for 60 minutes in a high temperature and high oxygen environment, and after annealing, close the oxygen valve and oxygen flow meter and cool naturally to room temperature; S3: The preparation steps of Cs3Cu2I5 thin film are as follows: S31: masking the target material after S24 treatment, placing it in a PLD preparation chamber with reference to steps S1 and S21, raising the growth temperature to 110°C, setting the pulse energy to 250mJ, and the frequency to 4Hz, bombarding the surface of the Cs3Cu2I5 target material, and monitoring the deposition thickness of the Cs3Cu2I5 film to 300nm through a film thickness monitor; S32: After the growth is completed, the deposited Cs3Cu2I5 / ZnGa2O4 heterojunction sample is taken out according to step S24; S4: The preparation steps of Au electrode are as follows: S41: placing the grown Cs3Cu2I5 / ZnGa2O4 heterojunction sample in the sample holder of the electron beam vacuum thermal evaporation equipment, fixing it with a mask, placing the sample holder in the vacuum chamber of the thermal evaporation equipment, placing Au particles in the evaporation boat, closing the chamber door, and turning on the mechanical pump and the molecular pump in turn to evacuate to a high vacuum state; S42: Wait until the vacuum degree reaches 4×10 -4 Below Pa, the Au particles were heated to a molten state using resistive heating, the evaporation rate was controlled at 0.1~0.5Å / s, and a 50nm Au electrode was evaporated.
[0007] Furthermore, the distance between the ZnGa2O4 target and the Al2O3 substrate is 5 cm.
[0008] Furthermore, the distance between the Cs3Cu2I5 target and the ZnGa2O4 film is 5 cm; the Cs3Cu2I5 target is pressed by mixing CsI:CuI in a molar ratio of 3:2 (both powders are purchased from Alfa Aesar with a purity of 99.998%).
[0009] Furthermore, the electrode is Au, and the purity of the metal Au used in the electrode is 99.999%.
[0010] The present invention has the following beneficial effects: the technical solution of the present invention has the advantages of realizing complex stoichiometric ratios, controllable film thickness, vacuum in-situ growth, and high film quality; and the preparation conditions of the photodetector are pollution-free and extremely environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Schematic diagram of the Cs3Cu2I5 / ZnGa2O4 heterojunction structure according to the present invention.
[0012] Figure 1 Middle: 1. Metal Au electrode, 2. Cs3Cu2I5 thin film, 3. ZnGa2O4 thin film, 4. Al2O3 substrate.
[0013] Figure 2 This is the energy band arrangement diagram of the Cs3Cu2I5 / ZnGa2O4 heterojunction structure based on the Anderson band model according to the present invention.
[0014] Figure 3 This is the spectral responsivity curve of the heterojunction detector, and the inset is the relative detectivity curve. DETAILED DESCRIPTION
[0015] The present invention provides a method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector, using ZnGa2O4 and Cs3Cu2I5 thin films prepared by prior art to solve the problems of low film quality, complex and polluting preparation method, and inability to achieve self-driving.
[0016] In order to better understand the above technical solution, a detailed description is given below.
[0017] A method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector, using laser pulse deposition technology to bombard the surface of Cs3Cu2I5 and ZnGa2O4 target materials in a high vacuum environment; growing an ultra-wide bandgap ZnGa2O4 film under vacuum conditions, that is, placing the target material in a vacuum growth chamber of a pulsed laser deposition system, bombarding the ZnGa2O4 target material with a high-power pulsed laser in a high-temperature environment to form a plasma plume, and finally directionally diffusing to the oxide layer after an adiabatic expansion process of the plasma. The ZnGa2O4 thin film is formed by nucleation and growth on an aluminum substrate. The deposited sample is then placed in a tube furnace (CVD) for high-temperature oxygen annealing to fill the oxygen vacancies. Subsequently, the Cs3Cu2I5 target is bombarded with a high-power pulsed laser again to form a Cs3Cu2I5 thin film. Finally, Au is evaporated onto the surface of Cs3Cu2I5 / ZnGa2O4 as an electrode in electron beam vacuum thermal evaporation through a mask plate to form Au-Cs3Cu2I5-Au and Au-ZnGa2O4-Au ohmic contacts.
[0018] Specific implementation method: A method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector is completed by the following steps: S1: The preparation steps for thin film preparation are as follows: First, select a double-sided polished Al2O3 substrate and ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 5 minutes, 5 minutes, and 10 minutes respectively, in order to clean the dirt on the surface of the Al2O3 substrate. Then blow it dry with nitrogen, place it on the sample holder and fix it with metal, open the PLD injection chamber with high-purity nitrogen, place the Al2O3 substrate and the sample holder in it, open the water tank, the injection chamber mechanical pump, the injection chamber vacuum gauge, and the injection chamber molecular pump in turn, quickly pump the injection chamber to a high vacuum state, and then proceed to the next step of the experiment; S2: The preparation steps of ZnGa2O4 thin film are as follows: S21: The vacuum degree in the injection chamber reaches 6×10 -5 After the temperature is below Pa, the plate valves of the injection chamber-transfer chamber and the transfer chamber-preparation chamber are opened in sequence, and the Al2O3 substrate and the sample holder in S1 are placed in the preparation chamber; S22: Then, the temperature of the preparation chamber cavity and the substrate temperature are raised to 500°C using the temperature raising program L-MBE, the temperature raising current is adjusted to 5A (100°C / 1A), the temperature raising rate is controlled at 10°C / min, and the preparation chamber ionization vacuum gauge is turned off at the same time, and the 248nm excimer laser is turned on for preheating; S23: After the temperature rises to 500°C and stabilizes for 10 minutes, the laser preheating is completed, the pulse energy is adjusted to 320mJ, the frequency is set to 8Hz, and then the ZnGa2O4 target material is bombarded. The bombarded plasma plume is deposited on the surface of the Al2O3 substrate under high temperature environment. The deposition thickness is controlled to be 500nm by observing the film thickness monitor, and a ZnGa2O4 thin film sample on the Al2O3 substrate is obtained; S24: After the deposition is completed, the laser is first turned off, the temperature is set to 0°C, and the current is adjusted to 0A. After the temperature drops below 100°C, the ionization vacuum gauge ionization switch is turned on, and then the preparation chamber-transfer chamber and transfer chamber-injection chamber plate valves are opened in sequence to send the sample into the injection chamber. The molecular pump and mechanical pump are closed in sequence and filled with high-purity nitrogen, and then the sample obtained in S23 is taken out as a whole; S25: Place the sample taken out in S24 in a tube furnace (CVD), evacuate to a vacuum state, introduce high-purity oxygen, control the oxygen flow rate at 30 SCCM and stabilize for 15 minutes, then use a program to control the gradient temperature to 800°C, anneal for 60 minutes in a high temperature and high oxygen environment, and after annealing, close the oxygen valve and oxygen flow meter and cool naturally to room temperature; S3: The preparation steps of Cs3Cu2I5 thin film are as follows: S31: masking the target material after S24 treatment, placing it in a PLD preparation chamber with reference to steps S1 and S21, raising the growth temperature to 110°C, setting the pulse energy to 250mJ, and the frequency to 4Hz, bombarding the surface of the Cs3Cu2I5 target material, and monitoring the deposition thickness of the Cs3Cu2I5 film to 300nm through a film thickness monitor; S32: After the growth is completed, the deposited Cs3Cu2I5 / ZnGa2O4 heterojunction sample is taken out according to step S24; S4: The preparation steps of Au electrode are as follows: S41: placing the grown Cs3Cu2I5 / ZnGa2O4 heterojunction sample in the sample holder of the electron beam vacuum thermal evaporation equipment, fixing it with a mask, placing the sample holder in the vacuum chamber of the thermal evaporation equipment, placing Au particles in the evaporation boat, closing the chamber door, and turning on the mechanical pump and the molecular pump in turn to evacuate to a high vacuum state; S42: Wait until the vacuum degree reaches 4×10 -4 Below Pa, the Au particles were heated to a molten state using resistive heating, the evaporation rate was controlled at 0.1~0.5Å / s, and a 50nm Au electrode was evaporated.
[0019] In the preliminary preparation work described in step S1 of this embodiment, the cleaning solution and cleaning sequence of the Al2O3 substrate can be adjusted according to actual conditions.
[0020] In this embodiment, the experimental instrument described in step S2 is pulsed laser deposition, and the experimental material is ZnGa2O4 target material. The above method can be used but is not limited to it.
[0021] In this embodiment, the experimental conditions described in step S3 are 250 mJ and 4 Hz, which can be adjusted according to the actual situation of the laser model.
[0022] In this embodiment, the purity of the Au particles described in step S4 is 99.999%. The experimental method is electron beam vacuum thermal evaporation, and electrode evaporation can be performed according to actual conditions.
[0023] The above is only an embodiment of the present invention. It should be pointed out that, for those skilled in the art, several improvements can be made without departing from the concept of the present invention, such as changing the thin film growth method, changing the thickness of the thin film material, changing the substrate material, etc. These improvements should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector, characterized in that: The steps include: S1: The preparation steps for thin film preparation are as follows: First, select a double-sided polished Al2O3 substrate and ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 5 minutes, 5 minutes, and 10 minutes respectively, in order to clean the dirt on the surface of the Al2O3 substrate. Then blow it dry with nitrogen, place it on the sample holder and fix it with metal, open the PLD injection chamber with high-purity nitrogen, place the Al2O3 substrate and the sample holder in it, open the water tank, the injection chamber mechanical pump, the injection chamber vacuum gauge, and the injection chamber molecular pump in turn, quickly pump the injection chamber to a high vacuum state, and then proceed to the next step of the experiment; S2: The preparation steps of ZnGa2O4 thin film are as follows: S21: The vacuum degree in the injection chamber reaches 6×10 -5 After the temperature is below Pa, the plate valves of the injection chamber-transfer chamber and the transfer chamber-preparation chamber are opened in sequence, and the Al2O3 substrate and the sample holder in S1 are placed in the preparation chamber; S22: Then, the temperature of the preparation chamber cavity and the substrate temperature are raised to 500°C using the temperature raising program L-MBE, the temperature raising current is adjusted to 5A (100°C / 1A), the temperature raising rate is controlled at 10°C / min, and the preparation chamber ionization vacuum gauge is turned off at the same time, and the 248nm excimer laser is turned on for preheating; S23: After the temperature rises to 500°C and stabilizes for 10 minutes, the laser preheating is completed, the pulse energy is adjusted to 320mJ, the frequency is set to 8Hz, and then the ZnGa2O4 target material is bombarded. The bombarded plasma plume is deposited on the surface of the Al2O3 substrate under high temperature environment. The deposition thickness is controlled to be 500nm by observing the film thickness monitor, and a ZnGa2O4 thin film sample on the Al2O3 substrate is obtained; S24: After the deposition is completed, the laser is first turned off, the temperature is set to 0°C, and the current is adjusted to 0A. After the temperature drops below 100°C, the ionization vacuum gauge ionization switch is turned on, and then the preparation chamber-transfer chamber and transfer chamber-injection chamber plate valves are opened in sequence to send the sample into the injection chamber. The molecular pump and mechanical pump are closed in sequence and filled with high-purity nitrogen, and then the sample obtained in S23 is taken out as a whole; S25: Place the sample taken out in S24 in a tube furnace (CVD), evacuate to a vacuum state, introduce high-purity oxygen, control the oxygen flow rate at 30 SCCM and stabilize for 15 minutes, then use a program to control the gradient temperature to 800°C, anneal for 60 minutes in a high temperature and high oxygen environment, and after annealing, close the oxygen valve and oxygen flow meter and cool naturally to room temperature; S3: The preparation steps of Cs3Cu2I5 thin film are as follows: S31: masking the target material after S24 treatment, placing it in a PLD preparation chamber with reference to steps S1 and S21, raising the growth temperature to 110°C, setting the pulse energy to 250mJ, and the frequency to 4Hz, bombarding the surface of the Cs3Cu2I5 target material, and monitoring the deposition thickness of the Cs3Cu2I5 film to 300nm through a film thickness monitor; S32: After the growth is completed, the deposited Cs3Cu2I5 / ZnGa2O4 heterojunction sample is taken out according to step S24; S4: The preparation steps of Au electrode are as follows: S41: placing the grown Cs3Cu2I5 / ZnGa2O4 heterojunction sample in the sample holder of the electron beam vacuum thermal evaporation equipment, fixing it with a mask, placing the sample holder in the vacuum chamber of the thermal evaporation equipment, placing Au particles in the evaporation boat, closing the chamber door, and turning on the mechanical pump and the molecular pump in turn to evacuate to a high vacuum state; S42: Wait until the vacuum degree reaches 4×10 -4 Below Pa, the Au particles were heated to a molten state using resistive heating, the evaporation rate was controlled at 0.1~0.5Å / s, and a 50nm Au electrode was evaporated.
2. The method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector according to claim 1, characterized in that: The Al2O3 substrate is used in step S1.
3. The method for preparing a Cs3Cu2I5 / ZnGa2O4 heterojunction self-driven ultraviolet photodetector according to claim 1, characterized in that: The pulse laser deposition technology is used in steps S2 and S3.
